Yoga And Indian Philosophy. - "Werner, Karel." (Delhi, 1980)
While Indian Philosophy has been in our time the object of mainly academic interest Yoga has become in recent decades and object of wide spread popular interest particularly in the west. But from at least the time of the Upanisads till Aurobindo Yoga has been an important source of inspiration to philosophy in Indian and philosophy in turn has often provided in turn has often provided an initial impetus and motivation for the practice of yoga and has produced various interpretations of Yogic experiences. It is therefore most appropriate that Yoga and Indian philosophy be given equal attention both in the context of academic research and in the framework of popularising Yoga.
Keywords: IndiaPhilosophy